A systematic review of the validity and reliability of patient‐reported experience measures. (19th June 2019) - Bull, Claudia; Byrnes, Joshua; Hettiarachchi, Ruvini; Downes, Martin
Abstract: Objectives: To identify patient‐reported experience measures (PREMs), assess their validity and reliability, and assess any bias in the study design of PREM validity and reliability testing. Data Sources/Study Setting: Articles reporting on PREM development and testing sourced from MEDLINE, CINAHL and Scopus databases up to March 13, 2018. Study Design: Systematic review. Data Collection/Extraction Methods: Critical appraisal of PREM study design was undertaken using the Appraisal tool for Cross‐Sectional Studies (AXIS). Critical appraisal of PREM validity and reliability was undertaken using a revised version of the COSMIN checklist. Principal Findings: Eighty‐eight PREMs were identified, spanning across four main health care contexts. PREM validity and reliability was supported by appropriate study designs. Internal consistency (n = 58, 65.2 percent), structural validity (n = 49, 55.1 percent), and content validity (n = 34, 38.2 percent) were the most frequently reported validity and reliability tests. Conclusions: Careful consideration should be given when selecting PREMs, particularly as seven of the 10 validity and reliability criteria were not undertaken in ≥50 percent of the PREMs. Testing PREM responsiveness should be prioritized for the application of PREMs where the end user is measuring change over time. Assessing measurement error/agreement of PREMs is important to understand the clinical relevancy of PREM scores used in a health care evaluation capacity.